A pediatric cystic fibrosis arthropathy case who responded to Elexacaftor/ Tezacaftor/Ivacaftor therapy - Arslan, Melikşah; Bahadır, Zeynep; Basiaga, Matthew L.; Chalmers, Sarah J.; Demirel, Nadir (Elsevier, 2023)
Cystic fibrosis arthropathy (CFA) is a transient, intermittent form of arthritis that cannot be associated with any other disease other than CF thus making CFA a diagnosis of exclusion. NSAIDs, short-term intermittent splinting, glucocorticoids, and disease-modifying anti-rheumatic drugs are treatment options for CFA. Currently, there is no consensus on how to best treat CFA. Diagnosis and treatment of CFA remain a challenge for physicians and people with CF. The newest CFTR modulator therapy, elexacaftor/tezacaftor/ivacaftor (ETI), was approved by the FDA recently for children over the age of 6 with at least one Phe508del allele in the CFTR gene. Multiple clinical benefits of ETI in pulmonary functions and overall disease burden have been reported since its approval, however, the data on the musculoskeletal therapeutic benefits of ETI has been limited. In this report, we present a 7-year-old female with CF whose CFA symptoms resolved after starting ETI therapy.
Keywords: Arthropathy; CFTR Modulators; Cystic Fibrosis; Elexacaftor/Tezacaftor/Ivacaftor; Inflammatory Arthritis; Musculoskeletal Symptoms; NSAIDs